Phosphors, Up Conversion Nano Particles, Quantum Dots and Their Applications Volume 2 - Liu, Ru-Shi (Springer Nature Singapore : Imprint: Springer, 2016)
This book introduces readers to fundamental information on phosphor and quantum dots. It comprehensively reviews the latest research advances in and applications of fluoride phosphors, oxide phosphors, nitridosilicate phosphors and various quantum dot materials. Phosphors and phosphor-based quantum dot materials have recently gained considerable scientific interest due to their wide range of applications in lighting, displays, medical and telecommunication technologies. This work will be of great interest to researchers and graduate students in materials sciences and chemistry who wish to learn more about the principles, synthesis and analysis of phosphors and quantum dot materials. .